Anaerobic soil disinfestation is an alternative to soil fumigation for control of some soilborne pathogens in strawberry production. (27th June 2017) - Shennan, C.; Muramoto, J.; Koike, S.; Baird, G.; Fennimore, S.; Samtani, J.; Bolda, M.; Dara, S.; Daugovish, O.; Lazarovits, G.; Butler, D.; Rosskopf, E.; et al.
Abstract : Alternatives to soil fumigation are needed for soilborne disease control. The aim of this study was to test anaerobic soil disinfestation (ASD) as an alternative to soil fumigation for control of critical soilborne pathogens in Californian strawberry production. Controlled environment experiments were conducted at 25 and 15 °C to test different materials as carbon sources for ASD using soil inoculated with Verticillium dahliae . Field trials were conducted in three locations comparing ASD with 20 Mg ha −1 rice bran (RB) against fumigated and untreated controls, steam, mustard seed meal and fish emulsion. In ASD‐treated soils, temperature and extent of anaerobic conditions were critical for control of V. dahliae, but multiple carbon inputs reduced inoculum by 80–100%. In field trials, ASD with RB provided control of a number of pathogens, and in three of four trials produced marketable fruit yields equivalent to fumigation. Little weed control benefit from ASD was found. ASD with RB also induced changes in the soil microbiome that persisted through the growing season. When equivalent yields were obtained, net returns above harvest and treatment costs with ASD RB were 92–96% of those with bed fumigation based on average prices over the previous 5 years. ASD can be a viable alternative for control of some soilborne pathogens. Growers are adopting ASD in California strawberry production, but research to determine optimal soil temperatures, anaerobicity thresholds and carbon sources for effective control of specific pathogens is needed.